Tenn. Pub. Acts 327, An Act To Repeal The Charter Of The Town Of Waverly, In Humphreys county, And to Incorporate Said Town And Define Its Rights, Powers, etc., §10 - (:unkn) unknown (My University, 1899)
Granted the town the authority to regulate the manufactories dangerous in causing or producing fires. Also allowed the town to prevent and suppress the sale of firearms and the carrying of concealed weapons.
Keywords: CARRY - CONCEALED; TRANSFER